2020
DOI: 10.1093/hmg/ddaa059
|View full text |Cite
|
Sign up to set email alerts
|

Ngly1 −/− rats develop neurodegenerative phenotypes and pathological abnormalities in their peripheral and central nervous systems

Abstract: N-glycanase 1 (NGLY1) deficiency, an autosomal recessive disease caused by mutations in the NGLY1 gene, is characterized by developmental delay, hypolacrima or alacrima, seizure, intellectual disability, movement disorders and other neurological phenotypes. Because of few animal models that recapitulate these clinical signatures, the mechanisms of the onset of the disease and its progression are poorly understood, and the development of therapies is hindered. In this study, we generated the systemic Ngly1-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 45 publications
7
69
0
Order By: Relevance
“…As for the inhibitor treatment experiments, ER stress markers or ROS production were determined and found not to be altered in NGLY1 KD relative to control (Fig 3d,e). This result agrees with previous studies carried out on NGLY1 KD in Drosophila melanogaster (Owings et al, 2018) and in NGLY1 knockout (KO) rats (Asahina et al, 2020) where no evidence of induction of ER stress was found. In addition, the rat model showed evidence for the accumulation of polyubiquitinated proteins in neurons from five-week-old NGLY1 KO rats (Asahina et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As for the inhibitor treatment experiments, ER stress markers or ROS production were determined and found not to be altered in NGLY1 KD relative to control (Fig 3d,e). This result agrees with previous studies carried out on NGLY1 KD in Drosophila melanogaster (Owings et al, 2018) and in NGLY1 knockout (KO) rats (Asahina et al, 2020) where no evidence of induction of ER stress was found. In addition, the rat model showed evidence for the accumulation of polyubiquitinated proteins in neurons from five-week-old NGLY1 KO rats (Asahina et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…This result agrees with previous studies carried out on NGLY1 KD in Drosophila melanogaster (Owings et al, 2018) and in NGLY1 knockout (KO) rats (Asahina et al, 2020) where no evidence of induction of ER stress was found. In addition, the rat model showed evidence for the accumulation of polyubiquitinated proteins in neurons from five-week-old NGLY1 KO rats (Asahina et al, 2020). The study in the Drosophila model also showed evidence for cnc (fly ortholog of NRF1) dysfunction by transcriptome analysis among downregulated genes (such as those encoding for proteasomal subunits) and an upregulation of the heat shock response (Owings et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…While perturbations to ERAD often result in ER stress, we have previously reported that there was no functional or transcriptome evidence for ER stress in a Drosophila model of NGLY1 deficiency ( Owings et al, 2018 ). Others have reported no ER stress in NGLY1 -/- human cells, mice, and rats ( Asahina et al, 2020 ; Mueller et al, 2020 ; Tambe et al, 2019 ). However, there is conflicting evidence for ER stress as it was recently reported that ER stress markers were upregulated in NGLY -/- MEFs ( Galeone et al, 2020 ).…”
Section: Discussionmentioning
confidence: 95%
“…These results were consistent with previous observations for Engase Ngly1 double-KO mice 28 ) or Ngly1 −/− rat. 30 )…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Ngly1 −/− rats develop neurological symptoms that are similar to subjects with NGLY1 deficiency. 30 ) In contrast, the smaller size of mice also offers some advantages in drug development, because lower drug dosages and smaller breeding spaces are needed. Accordingly, they are much more cost-effective for use.…”
Section: Introductionmentioning
confidence: 99%